Company Value Analysis of Automotive Subsector Companies Listed on the Indonesia Stock Exchange - Wikartika, Ira (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to examine, evaluate, and establish how business size, leverage, and liquidity affect firm value. This research employs a quantitative methodology. The study's population consists of the 15 automotive subsector businesses that were listed on the Indonesia Stock Exchange (IDX) between 2017 and 2019. Using the purposive sampling method, the sampling procedure produced a sample of fourteen enterprises. With the aid of SPSS 25, the hypothesis was investigated via the Multiple Linear Regression Analysis method. Firm Value served as the dependent variable in this study, whereas Liquidity, Leverage, and Firm Size served as independent factors. The study's conclusions show that while leverage had no bearing on business value, firm size and liquidity did